Combination Therapy of Alpha-Lipoic Acid, Gliclazide and Ramipril Protects Against Development of Diabetic Cardiomyopathy via Inhibition of TGF-β/Smad Pathway - Dugbartey, George J.; Wonje, Quinsker L.; Alornyo, Karl K.; Robertson, Louis; Adams, Ismaila; Boima, Vincent; Mensah, Samuel D. (Frontiers in Pharmacology, 2022)
Background Diabetic cardiomyopathy (DCM) is a major long-term complication of diabetes mellitus, accounting for over 20% of annual mortality rate of diabetic patients globally. Although several existing anti-diabetic drugs have improved glycemic status in diabetic patients, prevalence of DCM is still high. This study investigates cardiac effect of alpha-lipoic acid (ALA) supplementation of anti-diabetic therapy in experimental DCM. Methods Following 12 hours of overnight fasting, 44 male Sprague Dawley rats were randomly assigned to two groups of healthy control (n=7) and diabetic (n=37) groups, and fasting blood glucose was measured. Type 2 diabetes mellitus (T2DM) was induced in diabetic group by intraperitoneal (i.p.) administration of nicotinamide (110 mg/kg) and streptozotocin (55 mg/kg). After confirmation of T2DM on day 3, diabetic rats received monotherapies with ALA (60 mg/kg; n=7), gliclazide (15 mg/kg; n=7), ramipril (10 mg/kg; n=7) or combination of the three drugs (n=7) for 6 weeks while untreated diabetic rats received distilled water and were used as diabetic control (n=9). Rats were then sacrificed, and blood, pancreas and heart tissues were harvested for analyses using standard methods. Results T2DM induction caused pancreatic islet destruction, hyperglycemia, weight loss, high relative heart weight, and development of DCM, which was characterized by myocardial degeneration and vacuolation, cardiac fibrosis, elevated cardiac damage markers (plasma and cardiac creatine kinase-myocardial band, brain natriuretic peptide and cardiac troponin I). Triple combination therapy of ALA, gliclazide and ramipril preserved islet structure, maintained body weight and blood glucose level, and prevented DCM development compared to diabetic control (p<0.001). In addition, the combination therapy markedly reduced plasma levels of inflammatory markers (IL-1β, IL-6 and TNF-α), plasma and cardiac tissue malondialdehyde, triglycerides and total cholesterol while significantly increasing cardiac glutathione and superoxide dismutase activity and high-density lipoprotein-cholesterol compared to diabetic control (p<0.001). Mechanistically, induction of T2DM upregulated cardiac expression of TGF-β1, phosphorylated Smad2 and Smad3 proteins, which were downregulated following triple combination therapy (p<0.001). Conclusion Triple combination therapy of ALA, gliclazide and ramipril prevented DCM development by inhibiting TGF-β1/Smad pathway. Our findings can be extrapolated to the human heart, which would provide effective additional pharmacological therapy against DCM in T2DM patients.